Process Performance of Electrocoagulation in Treating Sanitary Landfill Leachate as Pretreatment Unit - Amanullah, Helmi (2018)
Since leachate treatment requires multiple stages of treatment, electrocoagulation (EC) is proposed as a pretreatment unit to compliment the main unit operations treatment such as membrane or biological treatment. EC was proposed in this study to overcome some of the problems with conventional treatments. The landfill leachate sample was collected from Pulau Burung Sanitary Landfill. In this study, variables of the EC process such as current density, EC time and types of electrode were optimized. Besides that, Cu and As removals also been studied since these heavy metals was hardly investigated by others researchers. The process efficiency of the EC was determined by percentage removal of chemical oxygen demand (COD), total suspended solids (TSS) and turbidity. The addition of cationic polyacrylamide (cPAM) as a coagulant aid was also studied in order to increase the efficiency of the treatment process. The results were further optimized using Response Surface Method (RSM).According to the results also, the use of cPAM increased the removal efficiency by (6%, 28% and 20%) COD, TSS and turbidity respectively compared to those of EC alone (39 %, 43% and 68%). Next, the particle sizes distribution also showned that cPAM had larger sizes (56.85μm) compared to EC alone (25.39μm). Total organic carbon (TOC) was also studied and the results showed that cPAM addition reduced the TOC by (44 mg/l) compared to EC alone (26 mg/l). Based on the results, EC was improved by the addition of cPAM. This was because cPAM improved the bridging, charge neutralization and agglomeration of coagulant agents with the pollutants. As a conclusion, EC was suitable as a pretreatment unit for leachate treatment.